Comparative life cycle assessment of copper and gold recovery from waste printed circuit boards: pyrometallurgy, chemical leaching and bioleaching - Schwartz, Eric; He, Haoyang; Nguyen, Bichlien; Frost, Kali; Ogunseitan, Oladele A.; Schoenung, Julie M. (Journal of Hazardous Materials, 2024)
Printed circuit boards (PCBs) make up a substantial amount of electronic waste (e-waste) generated annually. Waste PCBs contain high quantities of copper and gold in comparison to natural ores. As such, “urban mining” of waste PCBs to recover these metals is of commercial interest. In this work, we used life cycle assessment to compare the environmental impact of four copper and gold recovery processes. We evaluated pyrometallurgy, chemical leaching, and bioleaching, as well as a hybrid leaching process that uses bioleaching to recover copper and chemical leaching to recover gold. Furthermore, we considered differences in environmental impact based on differences in electricity sources. If electricity comes from fossil fuels, the pyrometallurgical process results in the lowest environmental impact in all impact categories studied. If electricity comes from carbon-free sources, the pyrometallurgical process results in the lowest environmental impact in all categories studied except global warming, where the hybrid leaching process results in the lowest impact. In all cases, metal recovery from waste PCBs leads to lower environmental impact than primary metal production. Our goal is to guide e-waste recyclers towards more environmentally sustainable metal recovery processes and to provide knowledge gaps in the field to guide future research.